fMRI Reveals Mitigation of Cerebrovascular Dysfunction by Bradykinin Receptors 1 and 2 Inhibitor Noscapine in a Mouse Model of Cerebral Amyloidosis - Ni, Ruiqing; Kindler, Diana Rita; Waag, Rebecca; Rouault, Marie; Ravikumar, Priyanka; Nitsch, Roger; Rudin, Markus; Camici, Giovanni G.; Liberale, Luca; Kulic, Luka; Klohs, Jan (Frontiers in Aging Neuroscience, 2019)
Functional magnetic resonance imaging (fMRI) techniques can be used to assess cerebrovascular dysfunction in Alzheimer’s disease, an important and early contributor to pathology. We hypothesized that bradykinin receptors inhibition alleviates the vascular dysfunction in a transgenic arcAβ mouse model of cerebral amyloidosis and that fMRI techniques can be used to monitor the treatment response. Using an enzyme immunoassay we detected increased bradykinin plasma levels in arcAβ mice as compared to non-transgenic littermates. Transgenic arcAβ mice, and non-transgenic littermates of 14 months-of-age were either treated with the bradykinin receptor 1 and 2 blocker noscapine or received normal drinking water as control over three months (n = 8-11/group) and all mice were assessed using fMRI at the end of the treatment period. Perfusion MRI using an arterial spin labeling technique showed regional hypoperfusion in arcAβ compared to non-transgenic controls, which was alleviated by noscapine treatment. Similarly, measuring cerebral blood volume changes upon pharmacological stimulation using vessel dilator acetazolamide revealed recovery of regional impairment of cerebral vascular reactivity in arcAβ mice upon noscapine treatment. In addition, we assessed with immunohistochemistry beta-amyloid (Aβ) and inflammation levels in brain sections. Staining for Aβ deposition (6E10) and related microgliosis (Iba1) in the cortex and hippocampus were found comparable between noscapine-treated and untreated arcAβ mice. In summary, bradykinin receptors blockage recovered cerebral vascular dysfunction but did not alter microgliosis and Aβ levels. fMRI method revealed the functional deficit in disease condition and was a useful tool to monitor the treatment response.